"It's how we deal": Perceptions of LGB peers' use of alcohol and other drugs to cope and sexual minority adults' own coping motivated substance use following the Pulse nightclub shooting. (February 2017) - Boyle, Sarah C.; LaBrie, Joseph W.; Costine, Lauren D.; Witkovic, Yong D.
Abstract: Sexual minority stress experiences (e.g. prejudice, victimization, etc.) and peer substance use norms (e.g. peers' frequency of use and quantity consumed) are important correlates of alcohol and drug use in sexual minority populations. The current study incorporates both of these by examining LGB individuals' perceptions of peers' use of alcohol and other drugs to cope with a sexual minority stressor, and whether perceptions of peer coping norms relate to one's own coping-motivated substance use in response to the stressor. Three-hundred and seven sexual minority males and females who identified as gay, lesbian, or bisexual completed an online survey approximately 1 month following the Pulse Nightclub Shooting, the deadliest incident of violence against LGBT people in U.S. history, and a stressor experienced within LGB communities throughout the U.S. Results revealed that LGB peers were widely perceived as likely to have coped with alcohol (68%) and drugs (41%) following the Pulse Shooting; however only small proportions of participants themselves reported coping with alcohol (26%) and drugs (7%). Further, multivariate models revealed that even after controlling for other factors including the stress impact of the Pulse shooting, the odds of using alcohol to cope with this event were 15 times greater among participants who held the perception that LGB peers likely used alcohol to cope relative to those who did not share this perception. Similarly, the odds of using drugs to cope with this event were 9 times greater among participants who perceived LGB peers likely to use drugs to cope with Pulse compared to those who did not. Importantly, these findings suggest that personalized normative feedback designed to correct perceptions of peers' coping motivated substance use may have utility as a motivational component in larger interventions seeking to reduce LGBs' substance use. Highlights: LGB adults were surveyed following the Pulse Nightclub Shooting. Participants widely perceived LGB peers to have coped by using alcohol and other drugs. Peer coping norms were strongly related to coping-motivated substance use, even after controlling for the stress impact of Pulse. LGB peer coping norms may be important targets for interventions.